Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pntd.0010073
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and case fatality rate of Enterovirus D68 infections, a systematic review and meta-analysis

Abstract: A substantial amount of epidemiological data has been reported on Enterovirus D68 (EV-D68) infections after the 2014 outbreak. Our goal was to map the case fatality rate (CFR) and prevalence of current and past EV-D68 infections. We conducted a systematic review (PROSPERO, CRD42021229255) with published articles on EV-68 infections in PubMed, Embase, Web of Science and Global Index Medicus up to January 2021. We determined prevalences using a model random effect. Of the 4,329 articles retrieved from the databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 162 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…Using a modified WGS approach, we were able to obtain near-complete EV-D68 genomes from a wide range of Ct values, including Ct values >30 and sample material, including CSF. The summer/autumn seasonal circulation is well recognized for all enteroviruses in temperate climates, with a biennial recurrence of EV-D68 observed in North America and Europe ( Elrick et al, 2021 ; Fall et al, 2022 ). Interestingly, our data shows a general shift towards the later months, with the upsurge emerging in an odd year ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a modified WGS approach, we were able to obtain near-complete EV-D68 genomes from a wide range of Ct values, including Ct values >30 and sample material, including CSF. The summer/autumn seasonal circulation is well recognized for all enteroviruses in temperate climates, with a biennial recurrence of EV-D68 observed in North America and Europe ( Elrick et al, 2021 ; Fall et al, 2022 ). Interestingly, our data shows a general shift towards the later months, with the upsurge emerging in an odd year ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet in just the past few years, there have been nationwide and global instances of morbidity and mortality due to non-reportable pathogens known to seasonally circulate (e.g. multiple adenoviruses and adeno-associated virus [58], EV-D68 [11,59,60]). Wastewater testing as an early warning system for viral outbreaks has been suggested by several teams, starting in the early 1940’s [61], but very purposefully implemented during the ongoing COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated 13 published studies, showing that the positive rate of EV-D68 antibody was relatively high, with 74.4% (95% CI: 66.9–82.0%) in the general population and 72.6% (95% CI: 61.6–83.7%) in the Chinese population. In another systematic study, the researchers found that the prevalence of previous EV-D68 infection was 66.3% (95% CI: 40.0–88.2), while the overall prevalence of current EV-D68 infection was 4% in apparently healthy individuals and patients with acute respiratory infection, AFM, and asthma-related illness [ 21 ]. Both the prevalence rate and severe disease rates were much lower than the seropositivity rate of EV-D68 in this study, indicating that the virus may spread silently, and serological data may better reflect the regional epidemic situation of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is a lack of systematic and comprehensive surveillance and documentation of EV-D68 prevalence globally, and latent infection of EV-D68 is not being taken seriously. Acute flaccid paralysis caused by EV-D68 infection is increasing, and there is currently a lack of effective drugs and vaccines against the virus [ 6 , 20 , 21 ]. Therefore, it is very important to further strengthen the understanding of virus serology for disease prevention.…”
Section: Introductionmentioning
confidence: 99%